(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2021)
Robo is a widely consumed Nigeria snack made from local food ingredients. Snacks are often subjectively classified as junk food, possibly because they naturally have little or no nutritional value, and unhealthy snacks consumption are associated with the risk of developing non-communicable diseases. The effects of producing Robo from melon and groundnut seeds at different ratios from 20 to 50% wereevaluated for proximate composition, physicochemical/functional and sensory attributes. The results showed an increase in crude protein (38.56a - 42.8d), crude fiber(15.01±0.014d), fat content (35.20e) and ash content (18.02e), but decreased in moisture content (2.43a - 3.30e). Hardness properties decrease from (240a- 720e). Robo from blends of melon and groundnut seeds have improved sensory attributes in terms of flavour, crispness, taste and overall acceptability, particularly at supplementation of 60% melon and 40% groundnut seeds. Thus, improved Robo will increase consumer’s nutrients intake and prevent health problems associated with snack intake. Bangladesh J. Sci. Ind. Res.56(4), 263-270, 2021